Melatonin augments expression of the procollagen α1 (I) and α1 (III) genes in the infarcted heart scar of pinealectomized rats - Drobnik, Jacek; Olczak, S awomir; Owczarek, Katarzyna; Hrabec, Zbigniew; Hrabec, El bieta (Connective tissue research, 2010)
The pineal gland is involved in the regulation of collagen accumulation in peripheral wounds and scars of the infarcted heart. This study is aimed to provide an explanation of whether the pineal gland and melatonin (MLT) is involved in the regulation of α1 (I) and α1 (III) procollagen gene expression. A secondary aim is the investigation of whether the mechanism of changes could be explained by the direct influence of MLT on myofibroblasts isolated from the scar. Myocardial infarction was induced by left coronary artery ligation in all rats. Animals were divided into groups: control, vehicle-treated rats, those injected with MLT, sham-operated animals, pinealectomized (Px) rats, and Px rats injected with vehicle or treated with MLT. In the second part of the study, cells from the scar of the infarcted heart were isolated and cultured with MLT at concentrations of 10−7 and 10−9 M. Both α1 (I) and α1 (III) procollagen gene expressions were evaluated by reverse transcription-polymerase chain reaction. Neither MLT given to intact animals nor pinealectomy alone have an influence on procollagen gene expression. However, administration of MLT to the Px animals increased the expression of α1 (I) and α1 (III) procollagen genes. Cells isolated from the heart scar were identified as myofibroblasts. MLT did not influence collagen gene expression in cultured myofibroblasts. The results indicate that MLT has an influence on procollagen gene expression in Px animals. Because the pineal product does not have an influence on the myofibroblast of the scar, the indirect mechanism of MLT action is suggested. This study may have practical implications in patients with a low level of MLT (elderly subjects, patients treated with β-adrenergic blockers).